2012
DOI: 10.1002/msc.1005
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Swedish Rheumatic Disease Empowerment Scale, SWE‐RES‐23

Abstract: The results support the possibility of adapting the SWE-DES-23 for use in patients with rheumatic diseases. The SWE-RES-23 shows acceptable psychometric properties, in terms of construct validity and internal consistency reliability. To validate the SWE-RES-23 fully, further studies are needed, with a focus on test-retest correlations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 20 publications
2
49
0
1
Order By: Relevance
“…Most of the instruments in this study demonstrated good validity and reliability, like the SF-36 (Persson et al 1998, Sullivan et al 1995, the ASA-A (Söderhamn et al 1996a, Söderhamn et al 1996b acceptable validity and reliability (Arvidsson et al 2012). The reliability was not tested in this study.…”
Section: Validity and Reliabilitymentioning
confidence: 72%
See 1 more Smart Citation
“…Most of the instruments in this study demonstrated good validity and reliability, like the SF-36 (Persson et al 1998, Sullivan et al 1995, the ASA-A (Söderhamn et al 1996a, Söderhamn et al 1996b acceptable validity and reliability (Arvidsson et al 2012). The reliability was not tested in this study.…”
Section: Validity and Reliabilitymentioning
confidence: 72%
“…The items are scored on a 5 point Likert-scale ranging from strongly disagree (1) to strongly agree (5). A higher value indicated a stronger empowerment (Arvidsson et al 2012). Self-care was assessed by the Appraisal of Self-Care Agency Scale (ASA-A) which assesses self-care ability.…”
Section: Instrumentsmentioning
confidence: 99%
“…Higher scores suggest a greater level of perception of empowerment. According to previous research [22], we reasoned that self-efficacy and control over the disease should be positively related to perceived quality of life. So, to establish validity and test correlations between P-RES-8 scores and patients' self-perceived health status, the Portuguese validated version of the MOS SF-36 [24] questionnaire was used.…”
Section: Methodsmentioning
confidence: 98%
“…Although created as an empowerment measure in diabetes care, the DES has been translated into different languages and used in patients with other chronic conditions (e.g., end-stage renal disease [21]), including rheumatic diseases [22]. A modified version of the DES-SF was created in Korea (Health Empowerment Scale -K-HES), replacing the term "diabetes" by "health problems" and expanding the items to cover all kinds of health conditions that affect the elderly [23].…”
Section: Introductionmentioning
confidence: 99%
“…특히, 유방암 여성들은 자가관리를 위해서 동병상련을 나눌 수 있는 자조집단 활 동에 참여하고 [13], 유방암 인식 개선과 유방암 여성의 권익 향상을 위한 핑크리본 캠페인에 동참하고 있다 [14]. 유방암 [8,23,27], 여성성 수용 [28], 자기통제 [6,8,22,27,28], 자기효능 [17,19,23,27], 자기결정 [8,17,23] 으로 하였고, 이는 유방암으로 인해 손상된 여성성을 긍정적으로 회 복하고 목적 달성을 위하여 자율적인 선택을 시행하며 자신의 삶을 조절하고자 하는 주도적인 역량을 의미한다. 상호작용적 요인의 개 념적 지표는 가족 대인관계 [5,10], 동료 대인관계 [7,10,23,27], 의료 인 대인관계 [7,9,18,20,21] Figure 2).…”
unclassified